CRISPR-Cas phage defense systems and prophages in Candidatus Accumulibacter. (15th May 2023) - Deng, Xuhan; Yuan, Jing; Chen, Liping; Chen, Hang; Wei, Chaohai; Nielsen, Per H.; Wuertz, Stefan; Qiu, Guanglei
Highlights: Not all Ca. Accumulibacter had a CRISPR-Cas system. Different Ca . Accumulibacter showed distinct adaptivity to phage predation. Ca. Accumulibacter with CRISPR-Cas systems tend to dominate in the long term. CRISPR-Cas systems in Ca. Accumulibacter are active along an SBR cycle. A few prophages in Ca. Accumulibacter genomes can readily activated. Abstract: Candidatus Accumulibacter plays a major role in enhanced biological phosphorus removal (EBPR) from wastewater. Although bacteriophages have been shown to represent fatal threats to Ca. Accumulibacter organisms and thus interfere with the stability of the EBPR process, little is known about the ability of different Ca. Accumulibacter strains to resist phage infections. We conducted a systematic analysis of the occurrence and characteristics of clustered regularly interspaced short palindromic repeats and associated proteins (CRISPR-Cas) systems and prophages in Ca. Accumulibacter lineage members (43 in total, including 10 newly recovered genomes). Results indicate that 28 Ca . Accumulibacter genomes encode CRISPR-Cas systems. They were likely acquired via horizontal gene transfer, conveying a distinct adaptivity to phage predation to different Ca. Accumulibacter members. Major differences in the number of spacers show the unique phage resistance of these members. A comparison of the spacers in closely related Ca. Accumulibacter members from distinct geographical locations indicates that habitat isolation may have resulted in the acquisition of resistance to different phages by different Ca . Accumulibacter. Long-term operation of three laboratory-scale EBPR bioreactors revealed high relative abundances of Ca . Accumulibacter with CRISPSR-Cas systems. Their specific resistance to phages in these reactors was indicated by spacer analysis. Metatranscriptomic analyses showed the activation of the CRISPR-Cas system under both anaerobic and aerobic conditions. Additionally, 133 prophage regions were identified in 43 Ca. Accumulibacter genomes. Twenty-seven of them (in 19 genomes) were potentially active. Major differences in the occurrence of CRISPR-Cas systems and prophages in Ca. Accumulibacter will lead to distinct responses to phage predation. This study represents the first systematic analysis of CRISPR-Cas systems and prophages in the Ca. Accumulibacter lineage, providing new perspectives on the potential impacts of phages on Ca. Accumulibacter and EBPR systems. Graphical abstract: Image, graphical abstract